Analisis Cara Kerja Beauty Influencer Tasya Farasya Dengan Shopee Affiliate (Hukum Ekonomi Syariah) - Aisyah Fitrah Az-Zahra Dira; Madian Muhammad Muchlis (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The term affiliate activity refers to actions taken by two parties to establish a partnership and build a mutually beneficial relationship. Marketing tactics used by business people include Influencers who function as target audiences and segments that are targeted for product promotion and branding. The aim of this research is to understand how Influencer Tasya Farasya and the Shopee Affiliate Program work and explore the legal aspects of sharia business related to collaboration between Influencers and the Shopee Affiliate Program. Researchers use descriptive qualitative methods using internet searching research, namely the process of searching for data via internet media to obtain information based on references, journals, articles. In this research, it was concluded that if an Influencer promotes a product, the Influencer will direct potential buyers to the affiliate's URL address. When the affiliate URL is opened, potential buyers will be directed to the seller's product sales website. This affiliate cooperation practice uses a samsarah contract because it is a form of intermediary between the seller and the buyer. In view of Sharia Economic Law, the practice of collaboration between Influencers and the Shopee affiliate program is permitted because it meets the requirements and is in line with the Samsarah agreement.